2019
DOI: 10.1016/j.cmi.2018.12.014
|View full text |Cite
|
Sign up to set email alerts
|

mcr-1 facilitated selection of high-level colistin-resistant mutants in Escherichia coli

Abstract: a b s t r a c tObjectives: The mcr-1 gene is the first reported plasmid-mediated colistin resistance gene. It has caused worldwide concern about the colistin resistance in Gram-negative bacteria. The aim of this research was to study the impact of mcr-1 on the selection of high-level colistin resistance (HLCR) mutations in Escherichia coli and Klebsiella pneumoniae. Methods: We detected the HLCR mutation rates of Enterobacteriaceae strains (K. pneumoniae XH209, KP10, and E. coli Q3, ATCC 25922) and their trans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 15 publications
(25 reference statements)
1
11
0
Order By: Relevance
“…Generally, E. coli strains with the mcr-1 gene are characterized by the low-level colistin resistance with a minimum inhibitory concentration (MIC) in the range of 2-8 mg/l. Zhang et al (2019) have shown that the expression of the mcr-1 gene in E. coli led to a higher mutation rate in the chromosomal polymyxin resistance cascade genes and produced higher MIC values (≥ 64 mg/l).…”
Section: Colistin Resistance Mechanismsmentioning
confidence: 99%
“…Generally, E. coli strains with the mcr-1 gene are characterized by the low-level colistin resistance with a minimum inhibitory concentration (MIC) in the range of 2-8 mg/l. Zhang et al (2019) have shown that the expression of the mcr-1 gene in E. coli led to a higher mutation rate in the chromosomal polymyxin resistance cascade genes and produced higher MIC values (≥ 64 mg/l).…”
Section: Colistin Resistance Mechanismsmentioning
confidence: 99%
“…24,25,40,42 In addition, a very recent report showed that pmrAB mutations contribute to the selection of HLCR in E. coli. 31 Currently, HLCR mechanisms have been…”
Section: Discussionmentioning
confidence: 99%
“…Figure 1 and Supplementary Table S2 shows the domains of PmrA/PmrB and positions of induced mutations conferring colistin resistance in this study as well as previously published mutations. 24,25,31,39,40 After subculturing in the absence of colistin, the PmrB-sd mutants IND-91 and IND-107 showed no reduction of colistin MIC, suggesting that the acquisition of this resistance phenotype was stable.…”
Section: Mutations That Confer Hlcr In Induced Mutantsmentioning
confidence: 99%
See 1 more Smart Citation
“…It seems that K. pneumoniae is more likely to generate chromosomal mutations but is less likely to harbor mcr-1 compared to the phenomenon observed in E. coli. Nevertheless, a previous study showed that after a single overnight exposure to twofold minimum inhibitory concentrations (MICs) of colistin, mcr-1 facilitated the development of high-level colistin resistance (HLCR; MIC ≥ 32 mg/L) mutants in E. coli but did not affect the HLCR mutation rates in K. pneumoniae (Zhang et al, 2019). However, another study reported that MCR-negative strains could be induced to higher level of colistin resistance than MCR-positive strains after step-wise induction (Luo et al, 2019).…”
Section: Introductionmentioning
confidence: 99%